Studi Kasus Identifikasi dan Penanganan Kasus HIV/AIDS Di Kota Salatiga - Yoku, Enjelina Rosa Pebrianti (Universitas Muhammadiyah Surabaya, 2020)
Objective: This study aims to see how Salatiga’s goverment identificaton and they handles HIV/AIDS casesMethods: This study applies qualitative method by using Single Case Embedded Study Results: The results of this study showed that there are differences in the role of each institution that is Commission on AIDS, non-governmental organizations, health facilities, and citizen care AIDS contributes to the identification and handling of HIV/AIDS cases in the city of Salatiga besides the implementation of the program and identify the prevention of HIV/AIDS in Salatiga City refers to the local regulation of the city of Salatiga.Conclusion: The identification and handling of HIV/AIDS cases in Salatiga is conducted referring to local regulation of the city of Salatiga by integrating with hospitals, health centers, NGOS and key populations.